PEMBERDAYAAN LITERASI KEUANGAN DAN PENTINGNYA MENABUNG BAGI SISWA DI SDN 02 PAMPANGAN - Yuliastanty, Susy; Nazif, Hazlif; Zumiarti, Zumiarti; Surya, Rahmad; Sunreni, Sunreni; Begawati, Nova; Al Fasyah Juliyus, Faridj; Saputra, Yudi; Nanda, Nanda (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
The level of financial literacy in Indonesia is still relatively low, especially among young children, so educational efforts are needed to instill a basic understanding of wise financial management. This community service activity aims to improve the financial literacy of elementary school students through education on the importance of saving. The activity was carried out at SDN 02 Pampangan with the involvement of 78 students in grades 4, 5, and 6. The implementation method used an educational and participatory approach, in the form of interactive material delivery, a "Mini Store" simulation, quizzes, and practice making piggy banks from used materials. The results of the activity showed that the results of observations and a brief post-activity evaluation showed that the majority of students had understood the material presented. Approximately 85% of students were able to re-explain the importance of saving and its benefits for daily life. As many as 90% of students were also able to clearly differentiate between needs and wants, and understand how to manage pocket money simply. The majority of students understood basic financial concepts such as the difference between needs and wants, the importance of saving, and how to manage pocket money simply. The response from students and teachers was very positive, with the school continuing its initiative to implement the "Savings Day" program regularly. This activity has successfully made a real contribution in building healthy financial habits from an early age, and has shown that a contextual educational approach is effective in improving children's financial literacy.